Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jmgm.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the interactions between metaldehyde and acidic surface groups of activated carbon under different pH conditions

Abstract: Explaining the interactions between metaldehyde and acidic surface groups of activated carbon under different pH conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…A study conducted by Busquets et al 44 showed that metaldehyde adsorption onto activated carbon was independent of the carbon's specific surface area, which indicated that the adsorption mechanism was more complex than just physisorption. The results from this study also support those reported previously, including both a theoretical study 73 and a laboratory investigation 28 which indicated that metaldehyde adsorption involves hydrogen bonding with carbon surface functional groups, with or without mediation by water molecules. Other phenomena such as van der Waals interactions and the thermodynamic gradients may also be contributory mechanisms for metaldehyde adsorption.…”
Section: Heat Of Adsorptionsupporting
confidence: 90%
“…A study conducted by Busquets et al 44 showed that metaldehyde adsorption onto activated carbon was independent of the carbon's specific surface area, which indicated that the adsorption mechanism was more complex than just physisorption. The results from this study also support those reported previously, including both a theoretical study 73 and a laboratory investigation 28 which indicated that metaldehyde adsorption involves hydrogen bonding with carbon surface functional groups, with or without mediation by water molecules. Other phenomena such as van der Waals interactions and the thermodynamic gradients may also be contributory mechanisms for metaldehyde adsorption.…”
Section: Heat Of Adsorptionsupporting
confidence: 90%
“…The present methodology was also used to theoretically evaluate the molecular inclusion process between CLD and cyclodextrins [39]. In addition, Jáuregui-Haza et al [40] studied the guest-host complexes of 1-iodochlordecone and β-1-iodo-pentachlorocyclohexane with cyclodextrins to use them as radiotracers of organochlorine pesticides in polluted water.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Although Gibbs's free energy of association (∆G ASSOC ) is the thermodynamic criteria used to define the spontaneity of a process, the association energy (∆E ASSOC ) was used in this study. This criterion has been profusely used by previous researchers [22,23,29,30,34,35,39,40] since it is computationally simpler compared to ∆G, and it avoids having to calculate the association entropies. It is defined as ∆E ASSOC = E supermolecule − E ref , where E supermolecule is the energy of the formed molecular complex by the activated carbon model (with and without SGs) and the interacting in the studied system molecules (in this case: CLD, β-HCH, and water molecules) and E ref is the energy of the isolated molecules.…”
Section: Multiple Minima Hypersurface Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…These groups are known to affect the adsorption of organic compounds onto carbon (Stavropoulos et al, 2008). Previously, both a theoretical study (Ferino-Perez et al, 2019) and a laboratory investigation (Tao and Fletcher, 2013) suggested that metaldehyde adsorption involves hydrogen bonding with carbon surface functional groups, with or without mediation by water molecules. Thus, the reduced availability of these functional groups for metaldehyde to interact with, resulted in a lower capacity of the carbon for metaldehyde.…”
Section: Comparison Of Chemical and Thermal Regenerationmentioning
confidence: 99%